Penerapan Advanced Pid Tuning Pada Plant Yang Critically Stable: Height Levitation Pingpong Ball - M Iqbal Nugraha; Aan Febriansyah; A F Khoiri; D Pratama (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
PID controller is the most popular feedback controller in industry. It has been known that PID controller is capable to provide a good control performance despite having a simple algorithm and easy to understand. However, the most common problem of using this control system is that it is difficult to stipulate the most appropriate constants to each controller or tuning. This project implemented advanced PID tuning which involves several tuning methods to acquire best performance on system or plant which is volatile or critically stable such as controlling height levitation pingpong ball. The tuning methods used and compared were Ziegler-Nichols (ZN) and Chien-Hrones-Reswick (CHR). Tuning process and monitoring were performed in real time using Simulink-Arduino. Based on experimental result, CHR method gave better performance compared to ZN method. ZN resulted in overshoot, rise time, settling time, and steady state error of 48%, 0.85s, 3.8s, and ±2cm respectively, while CHR method resulted in overshoot, rise time, settling time, and steady state error of 14%, 1.15s, 1.4s, and ±1cm respectively.